Accuracy of Step Count Estimations in Parkinson’s Disease Can Be Predicted Using Ambulatory Monitoring - Shokouhi, Navid; Khodakarami, Hamid; Fernando, Chathurini; Osborn, Sarah; Horne, Malcolm (Frontiers in Aging Neuroscience, 2022)
Objectives There are concerns regarding the accuracy of step count in Parkinsons Disease (PD) when wearable sensors are used. In this study, it was predicted that providing the normal rhythmicity of walking was maintained the autocorrelation function used to measure step count would provide relatively low errors in step count. Methods Twenty-one normal walkers (10 without PD) and 27 abnormal walkers were videoed while wearing a sensor (Parkinsons KinetiGraph (PKG). Median Step count error rates were 3% in normal walkers but >3% in abnormal walkers. The simultaneous accelerometry data and data from a 6-day PKG were examined and revealed that the 5th percentile of the left-tail of the spectral entropy histogram predicted whether which subjects had low error rate on video recording. Subjects with low error rates had lower MDS-UPDRS III scores and UPDRS III Q10-14 scores than the high error rate counter parts who also had high freezing of gait scores. Results Periods when walking occurred were identified in a 6 day PKGs from 190 non PD subjects aged over 60 and 155 people with PD were examined and the 5th percentile of the left-tail of the spectral entropy histogram was extracted. Eighty-four percent of controls and 72% of people with PD had low predicted error rates. People with PD with low bradykinesia scores (measured by the PKG) had step counts similar to controls whereas those with high bradykinesia scores had step counts similar to those with high error rates. On subsequent PKGs, step counts increased when bradykinesia was reduced by treatment and decreased when bradykinesia increased. Amongst both control and people with PD, low error rates were associated with those who spent considerable time making walks of more than 1 minute duration. Conclusions Using a measure of the loss of rhythmicity in walking appears to be a useful method for detecting the likelihood of step count errors. Bradykinesia in subjects with low predicted step count errors is related to step count but when predicted step count errors are high the step count should be assessed with caution.